You are on page 1of 32

# 3

The Z Transform
Exercises 3.2.3
1(a)
F(z) =

k=0
(1/4)
k
z
k
=
1
1 1/4z
=
4z
4z 1
if | z |> 1/4
1(b)
F(z) =

k=0
3
k
z
k
=
1
1 3/z
=
z
z 3
if | z |> 3
1(c)
F(z) =

k=0
(2)
k
z
k
=
1
1 (2)/z
=
z
z + 2
if | z |> 2
1(d)
F(z) =

k=0
(2)
k
z
k
=
1
1 2/z
=
z
z 2
if | z |> 2
1(e)
Z{k} =
z
(z 1)
2
if | z |> 1
from (3.6) whence
Z{3k} = 3
z
(z 1)
2
if | z |> 1
2
u
k
= e
2kT
=
_
e
2T
_
k
whence
U(Z) =
z
z e
2T
c
Pearson Education Limited 2004
160 Glyn James: Advanced Modern Engineering Mathematics, Third edition
Exercises 3.3.6
3
Z{sin kT} =
1
2
z
z e
T

1
2
z
z e
T
=
z sin T
z
2
2z cos T + 1
4
Z{
_
1
2
_
k
} =
2z
2z 1
so
Z{y
k
} =
1
z
3

2z
2z 1
=
2
z
2
(2z 1)
Proceeding directly
Z{y
k
} =

k=3
x
k3
z
k
=

r=0
x
r
z
r+3
=
1
z
3
Z {x
k
} =
2
z
2
(2z 1)
5(a)
Z
_

1
5
_
=

r=0
_
1
5z
_
r
=
5z
5z + 1
| z |>
1
5
5(b)
{cos k} =
_
(1)
k
_
so
Z {cos k} =
z
z + 1
| z |> 1
6
Z
_
_
1
2
_
k
_
=
2z
2z 1
By (3.5)
Z
_
(a
k
)
_
=
z
z a
so
Z
_
(ka
k1
)
_
=
z
(z a)
2
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 161
thus
Z
_
(ka
k
)
_
=
az
(z a)
2
whence
Z
_
k
_
1
2
_
k
_
=
2z
(2z 1)
2
7(a)
sinh k =
1
2
(e

)
k

1
2
(e

)
k
so
Z {sinh k} =
1
2
_
z
z e

z
z e

_
=
z sinh
z
2
2z cosh + 1
7(b)
cosh k =
1
2
(e

)
k
+
1
2
(e

)
k
then proceed as above.
8(a)
u
k
=
_
e
4kT
_
=
_
e
4T
_
k
; Z {u
k
} =
z
z e
4T
8(b)
u
k
=
1
2
_
e
kT
e
kT
_
Z {u
k
} =
1
2
_
z
z e
T

z
z e
T
_
=
z sin T
z
2
2z cos T + 1
8(c)
u
k
=
1
2
_
e
2kT
+e
2kT
_
then proceed as above.
9 Initial value theorem: obvious from denition.
c
Pearson Education Limited 2004
162 Glyn James: Advanced Modern Engineering Mathematics, Third edition
9 Final value theorem
(1 z
1
)X(z) =

r=0
x
r
x
r1
z
r
= x
0
+
x
1
x
0
z
+
x
2
x
1
z
2
+. . . +
x
r
x
r1
z
r
+. . .
As z 1 and if
lim
r
x
r
exists, then
lim
z1
(1 z
1
)X(z) = lim
r
x
r
10 Multiplication property (3.19): Let Z {x
k
} =

k=0
x
k
z
k
= X(z) then
Z
_
a
k
x
k
_
=

k=0
a
k
x
k
z
k
= X(z/a)
10 Multiplication property (3.20)
z
d
dz
X(z) = z
d
dz

k=0
x
k
z
k
=

k=0
kx
k
z
k
= Z {kx
k
}
The general result follows by induction.
Exercises 3.4.2
11(a)
z
z 1
; from tables u
k
= 1
11(b)
z
z + 1
=
z
z (1)
; from tables u
k
= (1)
k
11(c)
z
z 1/2
; from tables u
k
= (1/2)
k
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 163
11(d)
z
3z + 1
=
1
3
z
z + 1/3

1
3
(1/3)
k
11(e)
z
z
; from tables u
k
= ( )
k
11(f )
z
z +

2
=
z
z (

2)
(

2)
k
11(g)
1
z 1
=
1
z
z
z 1

_
0; k = 0
1; k > 0
using rst shift property.
11(h)
z + 2
z + 1
= 1 +
1
z
z
z + 1

_
1; k = 0
(1)
k1
; k > 0
=
_
1; k = 0
(1)
k+1
; k > 0
12(a)
Y (z)/z =
1
3
1
z 1

1
3
1
z + 2
so
Y (z) =
1
3
z
z 1

1
3
z
z + 2

1
3
_
1 (2)
k
_
12(b)
Y (z) =
1
7
_
z
z 3

z
z + 1/2
_

1
7
_
(3)
k
(1/2)
k
_
12(c)
Y (z) =
1
3
z
z 1
+
1
6
z
z + 1/2

1
3
+
1
6
(1/2)
k
c
Pearson Education Limited 2004
164 Glyn James: Advanced Modern Engineering Mathematics, Third edition
12(d)
Y (z) =
2
3
z
z 1/2

2
3
z
z + 1

2
3
(1/2)
k

2
3
(1)
k
=
2
3
(1/2)
k
+
2
3
(1)
k+1
12(e)
Y (z) =
1
2
_
z
z

z
z ( )
_
=
1
2
_
z
z e
/2

z
z e
/2
_

1
2
_
(e
/2
)
k
(e
/2
)
k
_
= sin k/2
12(f )
Y (z) =
z
_
z (

3 + )
_ _
z (

3 )
_
=
1
2
_
z
z (

3 + )

z
z (

3 )
_
=
1
2
_
z
z 2e
/6

z
z 2e
/6
_

1
2
_
2
k
e
k/6
2
k
e
k/6
_
= 2
k
sin k/6
12(g)
Y (z) =
5
2
z
(z 1)
2
+
1
4
z
z 1

1
4
z
z 3

5
2
k +
1
4
_
1 3
k
_
12(h)
Y (z)/z =
z
(z 1)
2
(z
2
z + 1)
=
1
(z 1)
2

1
z
2
z + 1
so
Y (z) =
z
(z 1)
2

1

3
_
z
z
1+

3
2

z
z
1

3
2
_
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 165
=
z
(z 1)
2

1

3
_
z
z e
/3

z
z e
/3
_
k
2

3
sin k/3 = k +
2

3
cos(k/3 3/2)
13(a)
X(z) =

k=0
x
k
z
k
=
1
z
+
2
z
7
whence x
0
= 0, x
1
= 1, x
2
= x
3
= . . . = x
6
= 0, x
7
= 2 and x
k
= 0, k > 7.
13(b) Proceed as in Example 13(a).
13(c) Observe that
3z +z
2
+ 5z
5
z
5
= 5 +
1
z
3
+
3
z
4
and proceed as in Example 13(a).
13(d)
Y (z) =
1
z
2
+
1
z
3
+
z
z + 1/3
{0, 0, 1, 1} +{(1/3)
k
}
13(e)
Y (z) = 1 +
3
z
+
1
z
2

1/2
z + 1/2
{1, 3, 1}
1
2
_
0, k = 0
(1/2)
k
, k 1
=
_

_
1, k = 0
5/2, k = 1
5/4, k = 2

1
2
(1/2)
k1
, k 3
=
_

_
1, k = 0
5/2, k = 1
5/4, k = 2

1
8
(1/2)
k3
, k 3
c
Pearson Education Limited 2004
166 Glyn James: Advanced Modern Engineering Mathematics, Third edition
13(f )
Y (z) =
1
z 1

2
(z 1)
2
+
1
z 2

_
0, k = 0
1 2(k 1) + 2
k1
, k 1
=
_
0, k = 0
3 2k + 2
k1
, k 1
13(g)
Y (z) =
2
z 1

1
z 2

_
0, k = 0
2 2
k1
, k 1
Exercises 3.5.3
14(a) If the signal going into the left D-block is w
k
and that going into the right
D-block is v
k
, we have
y
k+1
= v
k
, v
k+1
= w
k
= x
k

1
2
v
k
so
y
k+2
= v
k+1
= x
k

1
2
v
k
= x
k

1
2
v
k
= x
k

1
2
y
k+1
i.e.
y
k+2
+
1
2
y
k+1
= x
k
14(b) Using the same notation
y
k+1
= v
k
, v
k+1
= w
k
= x
k

1
4
v
k

1
5
y
k
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 167
Then
y
k+2
= x
k

1
4
y
k+1

1
5
y
k
or
y
k+2
+
1
4
y
k+1
+
1
5
y
k
= x
k
15(a)
z
2
Y (z) z
2
y
0
zy
1
2(zY (z) zy
0
) +Y (z) = 0
with y
0
= 0, y
1
= 1
Y (z) =
z
(z 1)
2
so y
k
= k, k 0.
15(b) Transforming and substituting for y
0
and y
1
Y (z)/z =
2z 15
(z 9)(z + 1)
so
Y (z) =
3
10
z
z 9

17
10
z
z + 1
thus
y
k
=
3
10
9
k

17
10
(1)
k
, k 0
15(c) Transforming and substituting for y
0
and y
1
Y (z) =
z
(z 2 )(z + 2 )
=
1
4
_
z
z 2e
/2

z
z 2e
/2
_
thus
y
k
=
1
4
2
k
_
e
k/2
e
k/2
_
= 2
k1
sin k/2, k 0
c
Pearson Education Limited 2004
168 Glyn James: Advanced Modern Engineering Mathematics, Third edition
15(d) Transforming, substituting for y
0
and y
1
, and rearranging
Y (z)/z =
6z 11
(2z + 1)(z 3)
so
Y (z) = 2
z
z + 1/2
+
z
z 3
thus
y
k
= 2(1/2)
k
+ 3
k
, k 0
16(a)
6y
k+2
+y
k+1
y
k
= 3, y
0
= y
1
= 0
Transforming with y
0
= y
1
= 0,
(6z
2
+z 1)Y (z) =
3z
z 1
so
Y (z)/z =
3
(z 1)(3z 1)(2z + 1)
and
Y (z) =
1
2
z
z 1

9
10
z
z 1/3
+
2
5
z
z + 1/2
Inverting
y
k
=
1
2

9
10
(1/3)
k
+
2
5
(1/2)
k
16(b) Transforming with y
0
= 0, y
1
= 1,
(z
2
5z + 6)Y (z) = z + 5
z
z 1
whence
Y (z) =
5
2
z
z 1
+
7
2
z
z 3
6
z
z 2
so
y
k
=
5
2
+
7
2
(3)
k
6 (2)
k
16(c) Transforming with y
0
= y
1
= 0,
(z
2
5z + 6)Y (z) =
z
z 1/2
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 169
so
Y (z) =
4
15
z
z 1/2

2
3
z
z 2
+
2
5
z
z 3
whence
y
n
=
4
15
(1/2)
k

2
3
(2)
k
+
2
5
(3)
k
16(d) Transforming with y
0
= 1, y
1
= 0,
(z
2
3z + 3)Y (z) = z
2
3z +
z
z 1
so
Y (z) =
z
z 1

z
z
2
3z + 3
=
z
z 1

1

3j
_
z
z
3+

3j
2

z
z
3

3j
2
_
=
z
z 1

1

3j
_
z
z

3e
j/6

z
z

3e
j/6
_
so
y
n
= 1
2

3
(

3)
k
e
jn/6
e
jn/6
2j
= 1 2(

3)
n1
sin n/6
16(e) Transforming with y
0
= 1, y
1
= 2
(2z
2
3z 2)Y (z) = 2z
2
+z + 6
z
(z 1)
2
+
z
z 1
so
Y (z) =
z
z 2
+z
_
z + 5
(z 1)
2
(2z + 1)(z 2)
_
=
12
5
z
z 2

2
5
z
z + 1/2

z
z 1
2
z
(z 1)
2
so
y
n
=
12
5
(2)
n

2
5
(1/2)
n
1 2n
16(f ) Transforming with y
0
= y
1
= 0,
(z
2
4)Y (z) = 3
z
(z 1)
2
5
z
z 1
c
Pearson Education Limited 2004
170 Glyn James: Advanced Modern Engineering Mathematics, Third edition
so
Y (z) =
z
z 1

z
(z 1)
2

1
2
z
z 2

1
2
z
z + 2
and
y
n
= 1 n
1
2
(2)
n

1
2
(2)
n
17 Write the transformed equations in the form
_
z 3/2
0.21
1
z 1/2
__
c(z)
e(z)
_
=
_
zC
0
zE
0
_
Then
_
c(z)
e(z)
_
=
1
z
2
2z + 0/96
_
z 1/2
0.21
1
z 3/2
__
zC
0
zE
0
_
Solve for c(z) as
c(z) = 1200
z
z 1.2
+ 4800
z
z 0.8
and
C
k
= 1200(1.2)
k
+ 4800(0.8)
k
This shows the 20% growth in C
k
in the long term as required.
Then
E
k
= 1.5C
k
C
k+1
= 1800(1.2)
k
+ 7200(0.8)
k
1200(1.2)
k+1
4800(0.8)
k+1
Dierentiate wrt k and set to zero giving
0.6 log(1.2) + 5.6xlog(0.8) = 0 where x = (0.8/1.2)
k
Solving, x = 0.0875 and so
k =
log 0.0875
log(0.8/1.2)
= 6.007
The nearest integer is k = 6, corresponding to the seventh year in view of the
labelling, and C
6
= 4841 approx.
18 Transforming and rearranging
Y (z)/z =
z 4
(z 2)(z 3)
+
1
(z 1)(z 2)(z 3)
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 171
so
Y (z) =
1
2
z
z 1
+
z
z 2

1
2
z
z 3
thus
y
k
=
1
2
+ 2
k

1
2
3
k
19
I
k
= C
k
+P
k
+G
k
= aI
k1
+b(C
k
C
k1
) +G
k
= aI
k1
+ba(I
k1
I
k2
) +G
k
so
I
k+2
a(1 +b)I
k+1
+abI
k
= G
k+2
Thus substituting
I
k+2
I
k+1
+
1
2
I
k
= G
Using lower case for the z transform we obtain
(z
2
z +
1
2
)i(z) = (2z
2
+z)G+G
z
z 1
whence
i(z)/z = G
_
1
z
2
z +
1
2
+
2
z 1
_
= G
_
2
z 1
+
1
(z
1+
2
)(z
1
2
)
_
so
i(z) = G
_
2
z
z 1
+
2
2
_
z
z
1

2
e
/4

z
z
1

2
e
/4
__
Thus
I
k
= G
_
2 +
2
2
(
1

2
)
k
_
e
k/4
e
k/4
_
_
= 2G
_
1 +
_
1

2
_
k
sin k/4
_
c
Pearson Education Limited 2004
172 Glyn James: Advanced Modern Engineering Mathematics, Third edition
i
n+2
2 cosh i
n+1
+i
n
= 0
with cosh = 1 +R
1
/2R
2
. Transforming and solving for I(z)/z gives
I(z)/z =
zi
0
+ (i
1
2i
0
cosh )
(z e

)(z e

)
=
1
2 sinh
_
i
0
e

+ (i
1
2i
0
cosh )
z e

i
0
e

+ (i
1
2i
0
cosh )
z e

_
Thus
i
k
=
(i
0
e

+ (i
1
2i
0
cosh ))e
n
(i
0
e

+ (i
1
2i
0
cosh ))e
n
2 sinh
=
1
sinh
{i
1
sinh n i
0
sinh(n 1)}
Exercises 3.6.5
21 Transforming in the quiescent state and writing as Y (z) = H(z)U(z) then
21(a)
H(z) =
1
z
2
3z + 2
21(b)
H(z) =
z 1
z
2
3z + 2
21(c)
H(z) =
1 + 1/z
z
3
z
2
+ 2z + 1
22 For the rst system, transforming from a quiescent state, we have
(z
2
+ 0.5z + 0.25)Y (z) = U(z)
The diagram for this is the standard one for a second order system and is shown
in Figure 3.1 and where Y (z) = P(z), that is y
k
= p
k
.
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 173
Figure 3.1: The block diagram for the basic system of Exercise 22.
Transforming the second system in the quiescent state we obtain
(z
2
+ 0.5z + 0.25)Y (z) = (1 0.6)U(z)
Clearly
(z
2
+ 0.5z + 0.25)(1 0.6z)P(z) = (1 0.6z)U(z)
indicating that we should now set Y (z) = P(z) 0.6zP(z) and this is shown in
Figure 3.2.
Figure 3.2: The block diagram for the second system of Exercise 22
c
Pearson Education Limited 2004
174 Glyn James: Advanced Modern Engineering Mathematics, Third edition
23(a)
Y

(z)/z =
1
(4z + 1)(2z + 1)
so
Y

(z) =
1
2
z
z + 1/4

1
2
z
z + 1/2
y
k
=
1
2
(1/4)
k

1
2
(1/2)
k
23(b)
Y

(z)/z =
z
z
2
3z + 3
whence
Y

(z) =
3 +

3
2

3
z
z
(3+

3 )
2

3
2

3
z
z
(3

3 )
2
so
y
k
=
3 +

3
2

3
(

3)
k
e
k/6

3
2

3
(

3)
k
e
k/6
= 2(

3)
k
_

3
2
sin k/6 +
1
2
cos k/6
_
= 2(

3)
k
sin(k + 1)/6
23(c)
Y

(z)/z =
z
(z 0.4)(z + 0.2)
so
Y

(z) =
2
3
z
z 0.4
+
1
3
z
z + 0.2
then
y
k
=
2
3
(0.4)
k
+
1
3
(0.2)
k
23(d)
Y

(z)/z =
5z 12
(z 2)(z 4)
so
Y

(z) =
z
z 2
+ 4
z
z 4
and
y
k
= (2)
k
+ (4)
k+1
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 175
24(a)
Y

(z) =
1
z
2
3z + 2
=
1
z 2

1
z 1
y
k
=
_
0, k = 0
2
k1
1, k > 0
24(b)
Y

(z) =
1
z 2
so
y
k
=
_
0, k = 0
2
k1
, k > 0
25 Examining the poles of the systems, we nd
25(a) Poles at z = 1/3 and z = 2/3, both inside | z |= 1 so the system is
stable.
25(b) Poles at z = 1/3 and z = 2/3, both inside | z |= 1 so the system is
stable.
25(c) Poles at z = 1/2 1/2 , | z |= 1/

## 2, so both inside | z |= 1 and the

system is stable.
25(d) Poles at z = 3/4

## 17/4, one of which is outside | z |= 1 and so the

system is unstable.
25(e) Poles at z = 1/4 and z = 1 thus one pole is on | z |= 1 and the other is
inside and the system is marginally stable.
c
Pearson Education Limited 2004
176 Glyn James: Advanced Modern Engineering Mathematics, Third edition
26 To use the convolution result, calculate the impulse response as y
,k
(1/2)
k
.
Then the step response is
y
k
=
k

j=0
1 (1/2)
kj
= (1/2)
k
k

j=0
1 (2)
j
= (1/2)
k
1 (2)
k+1
1 2
= (1/2)
k
(2
k+1
1) = 2 (1/2)
k
Directly,
Y (z)/z =
z
(z 1/2)(z 1)
=
2
z 1

1
z 1/2
so
y
k
= 2 (1/2)
k
27 Substituting
y
n+1
y
n
+Ky
n1
= K/2
n
or
y
n+2
y
n+1
+Ky
n
= K/2
n+1
Taking z transforms from the quiescent state, the characteristic equation is
z
2
z +K = 0
with roots
z
1
=
1
2
+
1
2

1 4K and z
2
=
1
2

1
2

1 4K
For stability, both roots must be inside | z |= 1 so if K < 1/4 then
z
1
< 1
1
2
+
1
2

1 4K < 1 K > 0
and
z
2
> 1
1
2

1
2

1 4K > 1 k > 2
If K > 1/4 then
|
1
2
+
1
2

4K 1 |
2
< 1 K < 1
The system is then stable for 0 < K < 1.
When k = 2/9 we have
y
n+2
y
n+1
+
2
9
y
n
=
1
9
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 177
Transforming with a quiescent initial state
(z
2
z +
2
9
)Y (z) =
1
9
z
z 1/2
so
Y (z) = z
1
9
_
1
(z 1/2)(z 1/3)(z 2/3)
_
= 2
z
z 1/3
+ 2
z
z 2/3
4
z
z 1/2
which inverts to
y
n
= 2(1/3)
n
+ 2(2/3)
n
4(1/2)
n
28
z
2
+ 2z + 2 = (z (1 + ))(z (1 + ))
establishing the pole locations. Then
Y

(z) =
1
2
z
z (1 + )

1
2
z
z (1 )
So since (1 ) =

2e
3 /4
etc.,
y
k
= (

2)
k
sin 3k/4
Exercises 3.9.6
29
H(s) =
1
s
2
+ 3s + 2
Replace s with
2

z 1
z + 1
to give

H(z) =

2
(z + 1)
2
4(z 1)
2
+ 6(z
2
1) + 2
2
(z + 1)
2
=

2
(z + 1)
2
(4 + 6 + 2
2
)z
2
+ (4
2
8)z + (4 6 + 2
2
)
c
Pearson Education Limited 2004
178 Glyn James: Advanced Modern Engineering Mathematics, Third edition
This corresponds to the dierence equation
(Aq
2
+Bq +C)y
k
=
2
(q
2
+ 2q + 1)u
k
where
A = 4 + 6 + 2
2
B = 4
2
8 C = 4 6 + 2
2
Now put q = 1 + to get
(A
2

2
+ (2A+B) +A+B +C)y
k
=
2
(
2

2
+ 4 + 4)u
k
With t = 0.01 in the q form the system poles are at z = 0.9048 and z = 0.8182,
inside | z |= 1. When t = 0.01 these move to z = 0.9900 and z = 0.9802,
closer to the stability boundary. Using the form with t = 0.1, the poles are at
= 1.8182 and = 0.9522, inside the circle centre (10, 0) in the -plane
with radius 10. When t = 0.01 these move to = 1.9802 and = 0.9950,
within the circle centre (100, 0) with radius 100, and the closest pole to the
boundary has moved slightly further from it.
30 The transfer function is
H(s) =
1
s
3
+ 2s
2
+ 2s + 1
To discretise using the bi-linear form use s
2
T
z 1
z + 1
to give

H(z) =
T
3
(z + 1)
3
Az
3
+Bz
2
+Cz +D
and thus the discrete-time form
(Aq
3
+Bq
2
+Cq +D)y
k
= T
3
(q
3
+ 3q
2
+ 3q + 1)u
k
where
A = T
3
+ 4T
2
+ 8T + 8, B = 3T
3
+ 4T
2
8T 3,
C = 3T
3
4T
2
8T + 3, D = T
3
4T
2
+ 8T 1
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 179
To obtain the form use s
2
2 +
giving the transfer function as
(2 + )
3
A
3
+B
2
+C +D
This corresponds to the discrete-time system
(A
3
+B
2
+C +D)y
k
= (
3

3
+ 2
2

2
+ 4 + 8)u
k
where
A =
3
+ 4
2
+ 8 + 8, B = 6
2
+ 16 + 16,
C = 12 + 16, D = 8
31 Making the given substitution and writing the result in vector-matrix form
we obtain
x(t) =
_
0
2
1
3
_
x(t) +
_
0
1
_
u(t)
and
y(t) = [1, 0]x(t)
This is in the general form
x(t) = Ax(t) +bu(t)
y = c
T
x(t) +d u(t)
The Euler discretisation scheme gives at once
x((k + 1)) = x(k ) + [Ax(k ) +bu(k )]
Using the notation of Exercise 29 write the simplied form equation as
_

2
+
12 + 8
A
+
8
A
_
y
k
=
1
A
_

2
+ 4 + 4

u
k
Now, as usual, consider the related system
_

2
+
12 + 8
A
+
8
A
_
p
k
= u
k
c
Pearson Education Limited 2004
180 Glyn James: Advanced Modern Engineering Mathematics, Third edition
and introduce the state variables x
1
(k) = p
k
, x
2
(k) = p
k
together with the
redundant variable x
3
(k) =
2
p
k
. This leads to the representation
x(k) =
_
_
0 1

8
A

12 + 8
A
_
_
x(k) +
_
0
1
_
u(k)
y
k
=
__
4
A

8
2
A
2
_
,
_
4
A

(12 + 8)
2
A
2
__
x(k) +

2
A
u(k)
or
x(k + 1) = x(k) + [A()x(k) +bu(k)]
y
k
= c
T
()x(k) +d()u
k
Since A(0) = 4 it follows that using A(0), c(0) and d(0) generates the Euler
Scheme when x(k) = x(k) etc.
32(a) In the z form substitution leads directly to
H(z) =
12(z
2
z)
(12 + 5)z
2
+ (812)z
When = 0.1 this gives
H(z) =
12(z
2
z)
12.5z
2
+11.2z 0.1
(b) The form is given by replacing z by 1 + . Substitution and
rearrangement gives

H() =
12(1 + )

2
(12 + 5) +(812) + 12
when = 0.1 this gives

H() =
12(1 + 0.1)
1.25
2
11.2 + 12
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 181
Review exercises 3.10
1
Z {f(kT)} = Z {kT} = TZ {k} = T
z
(z 1)
2
2
Z
_
a
k
sin k
_
= Z
_
a
k
(e
k
e
k
)
2
_
=
1
2
Z
_
(ae

)
k
(ae

)
k
_
=
1
2
_
z
z ae

z
z ae

_
=
az sin
z
2
2az cos +a
2
3 Recall that
Z
_
a
k
_
=
z
(z a)
2
Dierentiate twice wrt a then put a = 1 to get the pairs
k
z
(z 1)
2
k(k 1)
2z
(z 1)
3
then
Z
_
k
2
_
=
2z
(z 1)
3
+
z
(z 1)
2
=
z(z + 1)
(z 1)
3
4
H(z) =
3z
z 1
+
2z
(z 1)
2
so inverting, the impulse response is
{3 + 2k}
c
Pearson Education Limited 2004
182 Glyn James: Advanced Modern Engineering Mathematics, Third edition
5
Y
STEP
(z) =
z
(z + 1)(z + 2)(z 1)
=
1
2
z
z + 1
+
1
3
z
z + 2
+
1
6
z
z 1
Thus
y
STEP,k
=
1
2
(1)
k
+
1
3
(2)
k
+
1
6
6
F(s) =
1
s + 1
=
1
s

1
s + 1
which inverts to
f(t) = (1 e
t
)(t)
where (t) is the Heaviside step function, and so

F(z) = Z {f(kT)} =
z
z 1

z
z e
T
Then
e
sT
F(s) f((t T))
which when sampled becomes f((k 1)T) and
Z {f((k 1)T)} =

k=0
f((k 1)T)
z
k
=
1
z

F(z)
That is
e
sT
F(s)
1
z

F(z)
So the overall transfer function is
z 1
z
_
z
z 1

z
z e
T
_
=
1 e
T
z e
T
7
H(s) =
s + 1
(s + 2)(s + 3)
=
2
s + 3

1
s + 2
y

(t) = 2e
3t
e
2t
{2e
3kT
e
2kT
}
so

H(z) = 2
z
z e
3T

z
z e
2T
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 183
8(a) Simple poles at z = a and z = b. The residue at z = a is
lim
za
(z a)z
n1
X(z) = lim
za
(z a)
z
n
(z a)(z b)
=
a
n
a b
The residue at z = b is similarly
b
n
b a
and the inverse transform is the sum
of these, that is
_
a
n
b
n
a b
_
8(b)
(i) There is a only double pole at z = 3 and the residue is
lim
z3
d
dz
(z 3)
2
z
n
(z 3)
2
=
_
n3
n1
_
(ii) There are now simple poles at z =
1
2

3
2
. The individual residues are
thus given by
lim
z(1/2

3/2 )

_
1
2

3
2

_
n

3
Adding these and simplifying in the usual way gives the inverse transform
as
_
2

3
sin n/3
_
9
H(z) =
z
z + 1

z
z 2
so
Y
STEP
(z) =
_
z
z + 1

z
z 2
_
z
z 1
=
3z
(z 1)(z + 1)(z 2)
=
3
2
z
z 1
+
1
2
z
z + 1
2
z
z 2
so
y
STEP,k
=
3
2
+
1
2
(1)
k
2
k+1
c
Pearson Education Limited 2004
184 Glyn James: Advanced Modern Engineering Mathematics, Third edition
10
Y (z) =
z
2
(z + 1)(z 1)

_
1
1
z
_
=
z
z + 1
so
y
k
= (1)
k
11
Y (z) =
z
2
(z )(z )

_
1
+
z
+

z
2
_
= 1
so
y
k
= {
k
} = {1, 0, 0, . . .}
The response of the system with H(z) =
z
(z )(z )
is clearly given by
Y (z) = 1/z , which transforms to
y
k
= {
k1
} = {0, 1, 0, 0, . . .}
12 From H(s) =
s
(s + 1)(s + 2)
the impulse response is calculated as
y

(t) = (2e
2t
e
t
) t 0
Sampling gives
{y

(nT)} =
_
2e
2nT
e
nTt
_
with z transform
Z {y

(nT)} = 2
z
z e
2T

z
z e
T
= D(z)
Setting Y (z) = TD(z)X(z) gives
Y (z) = T
_
2
z
z e
2T

z
z e
T
_
X(z)
Substituting for T and simplifying gives
Y (z) =
1
2
z
_
z 0.8452
z
2
0.9744z + 0.2231
_
X(z)
so
(z
2
0.9744z + 0.2231)Y (z) = (0.5z
2
0.4226z)X(x)
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 185
y
n+2
0.9744y
n+1
+ 0.2231y
n
= 0.5x
n+2
0.4226x
n+1
As usual (see Exercise 22), draw the block diagram for
p
n+2
0.9744p
n+1
+ 0.2231p
n
= x
n
then taking y
n
= 0.5p
n+2
0.4226p
n+1
y
n+2
0.9744y
n+1
+ 0.2231y
n
= 0.5p
n+4
0.4226p
n+3
0.9774(0.5p
n+3
0.4226p
n+2
) + 0.2231(0.5p
n+2
0.4226p
n+1
)
= 0.5x
n+2
0.4226x
n+1
13
y
n+1
= y
n
+av
n
v
n+1
= v
n
+bu
n
= v
n
+b(k
1
(x
n
y
n
) k
2
v
n
)
= bk
1
(x
n
y
n
) + (1 bk
2
)v
n
so
y
n+2
= y
n+1
+a[bk
1
(x
n
y
n
) + (1 bk
2
)v
n
]
(a) Substituting the values for k
1
and k
2
we get
y
n+2
= y
n+1
+
1
4
(x
n
y
n
)
or
y
n+2
y
n+1
+
1
4
y
n
=
1
4
x
n
Transforming with relaxed initial conditions gives
Y (z) =
1
(2z 1)
2
X(z)
c
Pearson Education Limited 2004
186 Glyn James: Advanced Modern Engineering Mathematics, Third edition
(b) When X(z) =
A
z 1
,
Y (z) =
A
4
_
4
z
z 1
4
z
z 1/2
2
z
(z 1/2)
2
_
then
y
n
=
A
4
_
4 4(1/2)
n
2n(1/2)
n1

## 14 Substitution leads directly to

y
k
2y
k1
+y
k2
T
2
+ 3
y
k
y
k1
T
+ 2y
k
= 1
Take the z transform under the assumption of a relaxed system to get
[(1 + 3Tz + 2T
2
)z
2
(2 + 3T)z + 1]Y (z) = T
2
z
3
z 1
The characteristic equation is thus
(1 + 3Tz + 2T
2
)z
2
(2 + 3T)z + 1 = 0
with roots (the poles)
z =
1
1 +T
, z =
1
1 + 2T
The general solution of the dierence equation is a linear combination of these
together with a particular solution. That is
y
k
=
_
1
1 +T
_
k
+
_
1
1 + 2T
_
k
+
This can be checked by substitution which also shows that = 1/2. The
condition y(0) = 0 gives y
0
= 0 and since y

(t)
y
k
y
k1
T
, y

(0) = 0
implies y
k1
= 0. Using these we have
+ +
1
2
= 0
(1 +T) +(1 + 2T) +
1
2
= 0
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 187
with solution = 1, = 1/2 so
y
k
=
_
1
1 +T
_
k
+
1
2
_
1
1 + 2T
_
k
+
1
2
The dierential equation is simply solved by inverting the Laplace transform
to give
y(t) =
1
2
(e
2t
2e
t
+ 1), t 0
Figure 3.3: Response of continuous and discrete systems in Exercise 14 over
10 seconds when T = 0.1
c
Pearson Education Limited 2004
188 Glyn James: Advanced Modern Engineering Mathematics, Third edition
Figure 3.4: Response of continuous and discrete systems in Exercise 14 over
10 seconds when T = 0.05
15 Substitution for s and simplifying gives
[(4 + 6T + 2T
2
)z
2
+ (4T
2
8)z + (4 6T + 2T
2
)]Y (z)
= T
2
(z + 1)
2
X(x)
The characteristic equation is
(4 + 6T + 2T
2
)z
2
+ (4T
2
8)z + (4 6T + 2T
2
) = 0
with roots
z =
8 4T
2
4T
2(4 + 6T + 2T
2
)
That is
z =
1 T
1 +T
and z =
2 T
2 +T
c
Pearson Education Limited 2004
Glyn James: Advanced Modern Engineering Mathematics, Third edition 189
The general solution of the dierence equation is then
y
k
=
_
1 T
1 +T
_
k
+
_
2 T
2 +T
_
k
+
This can be checked by substitution which also shows that = 1/2. The
condition y(0) = 0 gives y
0
= 0 and since y

(t)
y
k
y
k1
T
, y

(0) = 0
implies y
k1
= 0. Using these we have
+ +
1
2
= 0

1 +T
1 T
+
2 +T
2 T
+
1
2
= 0
with solution
=
1 T
2
=
2 T
2
Thus
y
k
=
1 T
2
_
1 T
1 +T
_
k
+
2 T
2
_
2 T
2 +T
_
k
+
1
2
Figure 3.5: Response of continuous and discrete systems in Exercise 15 over
10 seconds when T = 0.1
c
Pearson Education Limited 2004
190 Glyn James: Advanced Modern Engineering Mathematics, Third edition
Figure 3.6: Response of continuous and discrete systems in Exercise 14 over 10
seconds when T = 0.05
16
f(t) = t
2
, {f(k)} =
_
k
2

2
_
, k 0
Now
Z{k
2
} = z
d
dz
z
(z 1)
2
=
z(z + 1)
(z 1)
3
So
Z{k
2

2
} =
z(z + 1)
2
(z 1)
3
To get D-transform, put z = 1 + to give
F

() =
(1 + )(2 + )
2

3
Then the D-transform is
F

() = F

() =
(1 + )(2 + )

3
c
Pearson Education Limited 2004